Determinants of Disease Pattern and Related Behaviour of Under- Five Children in Rural Areas - Rahman, Latifa; Tarek, Monwar; Hakim, Maksumul; Zaman, Riffat; Jewel, Mehedi Hasan (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The causative factors of childhood mortality and morbidity are multiple. In the rural areas, most of the parents seek traditional rather than modern medical facilities. They seek treatment when symptoms get worse. Objective: To find out the pattern of morbidities and health seeking behaviour of under five children. In order to achieve the goal it was focused on some of the key factors that may be closely related with the pattern of morbidities and treatment seeking behaviour. Materials and Methods: This was a cross sectional descriptive study conducted from 15 October 2014 to 15 March 2015 in Mohishashi village of Dhamrai Upazila, Dhaka District and Balihati village of Saturia Upazila, Manikganj district. Sample size was 350, obtained by non-probability, purposive sampling technique. The study was conducted by using a verbal questionnaire which was semi-structured close-ended in nature and a measuring tape for Mid Upper Arm Circumference (MUAC). The people of some purposively selected villages were taken as sample, so the results can not be generalised for the rural communities of Bangladesh. Results: The findings revealed that the majority (62%) of the children became ill at least 3 times a year. Cough and cold were most common symptoms in 315(58.01%) cases. Varieties of healthcare facilities are available in the community, among those hospital/ clinic had been availed most often which account to 277(65.95%). Amongst study cases, 190(45.23%) cases availed this facility due to effective and safe treatment and 181(43.09%) due to easy availability of health care service. The immunization status of children were 349(99.71%), though 256 (73.14%) children were completely immunized and 93(26.57%) were incomplete due to age constrains or other reason. This study shows that 220 (62.86%) children had not been hospitalized since birth for any reason. Among the admitted children, 74 out of 130 (37.14%) received their treatment from government hospitals after being sick. Conclusion: This study indicates that the health seeking behaviour of the parents of under five children in Dhamrai and Saturia Upazila is satisfactory. In order to reduce unwanted and unacceptable child mortality it is needed to build a better concept of healthcare in the rural areas. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 55-60